2017
DOI: 10.1186/s12893-017-0258-2
|View full text |Cite
|
Sign up to set email alerts
|

Hypomagnesemia predicts postoperative biochemical hypocalcemia after thyroidectomy

Abstract: BackgroundTo investigate the role of magnesium in biochemical and symptomatic hypocalcemia, a retrospective study was conducted.MethodsLess-than-total thyroidectomy patients were excluded from the final analysis. Identified the risk factors of biochemical and symptomatic hypocalcemia, and investigated the correlation by logistic regression and correlation test respectively.ResultsA total of 304 patients were included in the final analysis. General incidence of hypomagnesemia was 23.36%. Logistic regression sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 26 publications
1
32
1
3
Order By: Relevance
“…In a previous paper, we reported hypomagnesemia (<0.7 mmol/L) to be a relatively common (12.9%) occurrence after thyroidectomy, and to be a strong predictor of post‐thyroidectomy hypocalcemia . Other authors have reported similar findings . In our previous paper, we examined the association between magnesium levels taken on the first postoperative day and incidence of biochemical and symptomatic hypocalcemia during the course of the 2‐night postoperative stay .…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…In a previous paper, we reported hypomagnesemia (<0.7 mmol/L) to be a relatively common (12.9%) occurrence after thyroidectomy, and to be a strong predictor of post‐thyroidectomy hypocalcemia . Other authors have reported similar findings . In our previous paper, we examined the association between magnesium levels taken on the first postoperative day and incidence of biochemical and symptomatic hypocalcemia during the course of the 2‐night postoperative stay .…”
Section: Introductionmentioning
confidence: 73%
“…hypocalcemia, as it was not an independent predictor when included with postoperative PTH levels in multivariate analysis; however, it was a significant predictor on univariate analysis. 16 Another potential issue with Wang's study, as well as some other studies, 13 was that only patients with abnormal calcium levels on POD1, or who became symptomatic, underwent further calcium measurements. Thus, it is possible many cases of biochemical hypocalcemia may have been missed, given that in many cases calcium levels may not drop below normal until POD2 or later.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations